Perancangan Modul Pengendali Menggunakan Microcontroller AT 89S52 pada Prototipe Alat Penimbang Otomatis - Lobes Herdiman; Irwan Iftadi; Erik Wahyu Kusumawati (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2009)
The competition on industry that being increase, and the rapidly development of industry, encourage the industrialization to move the production more effective and efficient, so can press down the production cost that have to paid. One of them is redesigning machine or production equipment that still have manually characteristic. This research was redesign the machine production that is scales tools which is moved manually, so this condition need a long time in scales process. Redesign the scales tools doing by using the automatic toward it. The method that was choosing is implementation the microcontroller system control technology.Microcontroller is IC that was function to control, give instruction and produce the signals that will send to infrared censor, optocoupler and relay to move conveyor motor and motor arm. Microcontroller used as controlling module system. This control module use OP AMP, ADC, relay, LDR and opto encourage working process. In the last design was produce prototype scales tools that give easily in scales process, so can accelerate prototype working process, production cost more cheap and increasing production capacity.